The role of radiation penetration in the energy budget of the snowpack at Summit, Greenland - P. Kuipers Munneke; M. R. van den Broeke; C. H. Reijmer; M. M. Helsen; W. Boot; M. Schneebeli; K. Steffen (The Cryosphere, 2009)
Measurements of the summer surface energy balance at Summit, Greenland, are presented (8 June–20 July 2007). These measurements serve as input to an energy balance model that searches for a surface temperature for which closure of all energy terms is achieved. A good agreement between observed and modelled surface temperatures was found, with an average difference of 0.45°C and an RMSE of 0.85°C. It turns out that penetration of shortwave radiation into the snowpack plays a small but important role in correctly simulating snow temperatures. After 42 days, snow temperatures in the first meter are 3.6–4.0°C higher compared to a model simulation without radiation penetration. Sensitivity experiments show that these results cannot be reproduced by tuning the heat conduction process alone, by varying snow density or snow diffusivity. We compared the two-stream radiation penetration calculations with a sophisticated radiative transfer model and discuss the differences. The average diurnal cycle shows that net shortwave radiation is the largest energy source (diurnal average of +61 W m−2), net longwave radiation the largest energy sink (−42 W m−2). On average, subsurface heat flux, sensible and latent heat fluxes are the remaining, small heat sinks (−5, −5 and −7 W m−2, respectively), although these are more important on a subdaily timescale.